Student Teams Achievement Divisions Type Cooperative Learning Model in Improving Arabic Language Learning Outcomes - Noor Azzah, Alifa; Muntaqo, Rifqi; Imron, Ali (DAS Institute, 2024)
Arabic is a must-learn for Muslims. Learning Arabic requires a learning model. The learning model has a determinant of the success of teaching and learning activities. One of them is the STAD (Student Teams Achievement Division) type cooperative learning model. Most students feel that learning Arabic seems boring because they are always faced with memorization. So with this learning model at MTs Ma’arif Tieng Wonosobo, it is hoped that it can be an alternative in learning Arabic at the tsanawiyah madrasah. Arabic language learning at MTs Ma’arif Tieng Wonosobo with a total of 34 students, 14 students became the control class and 14 students became the experimental class. Data analysis used the N-Gain test analysis technique and the T-test test with the analysis results in the N-Gain test of the control class of 0.292 and the experimental class of 0.669, thus the experimental class was higher than the control class. And for the results of the T-test because ,t-calculate. > ,t -table. = 13.809 > 2.738 with α = 0.01 and ,t -count. > ,t -table. = 13,809 > 2,036 with α = 0.05 The result is that there is a difference in students' Arabic learning outcomes which shows that this learning model is more effective than the learning model using the conventional model.